Lizzie at last - Mills, Claudia (New York : Hyperion Paperbacks for Children, 2002)
Lizzie, who has always been considered a nerd by the other kids, begins the seventh grade determined to change her image so that she can blend in better with the popular crowd.
Originally published: New York : Farrar, Straus & Giroux, 2000.
5.0
3-6
3-6
Wilson's Children
Wilson's Junior High School
Keywords: Popularity -- Fiction; Individuality -- Fiction; Schools -- Fiction; Popularity -- Fiction; Individuality -- Fiction; School stories